EDUCAÇÃO OPERÁRIA ANTI-IMPERIALISTA E ANTICAPITAL: REVISITANDO O LEGADO MARXISTA DE J. C. MARIÁTEGUI - Nemirovsky, Gabriel Gualhanone (2018)
The present paper fetches some contributions from J. C. Mariátegui addressed to the theoretical and scientific field of Education to aim the objective of presenting the need to develop the construction of class formation spaces to the popular and workers masses against the contradictions presented in thebourgeois mediation between labor andeducation For that, it was resorted a bibliographical analysis of the texts concerning “Temas de Educación”,“Ponto de vista Antiimperialista” e “Ideología y Política”, aiming to demonstrate the anti- imperialist and socialist positions of the Peruvian revolutionary intellectual and its concretion through the “Oficina de Autoeducación Obrera”. The accomplishment of this analysis allowed this research to consider, by one side, that within the bourgeoissocial classes’ school there is no room for workers and popular masses formation towards their emancipation from the alienated labor condition, and, on the other side, labor, in its immediate concrete expression, cannot accomplish per se the self-education of the masses and, therefore, it is needed the construction of autonomous spaces for classist formation in which the proper mediation between labor and education could be performed beyond capital.___O presente artigo recupera contribuições de J. C. Mariátegui endereçadas ao campo teórico- científico da Educação como objetivo de apresentar a necessidade de se desenvolver concretamente a construção de espaços de formação classista das massas operárias e populares diante das contradições presentes nas formas burguesas de mediação entre trabalho e educação. Para tanto, recorreu-se à análise bibliográfica de textos presentes nas obras “Temas de Educación”, “Ponto de Vista Anti-imperialista” e “Ideología y Política”, com a intenção de evidenciar o posicionamento anti-imperialista e socialista do intelectual revolucionário peruano, e sua cristalização na criação da “Oficina de Autoeducación Obrera”. A concretização dessa análise permitiu considerar, por um lado, que no interior da escola de classes, burguesa, não há espaço de formação das massas operárias e populares para sua emancipação da condição alienada de trabalho e, por outro lado, que o Trabalho, em sua expressão concreta imediata, não é capaz de realizar per se a autoeducação das massas e, por isso, se faz necessária a construção de espaços autônomos para a formação classista das massas, em que se realize a adequada mediação entre trabalho e educação para além do capital.